Promoting health knowledge through micro-credit programs: experience of BRAC, Bangladesh - Hadi, Abdullahel (BRAC Research and Evaluation Division (RED), 2019)
The paper aims to assess the contribution of micro-credit program in raising health knowledge among the poor women in rural Bangladesh. Data were collected from the 1998 sample survey of 500 mothers aged 15-49 who had at least one <5 year-old child. Findings revealed that the socio-demographic factors such as age of woman, land ownership of the family and occupation of husband had no association with the prevalence of maternal knowledge. The knowledge was much higher among credit forum participants than non-participants although exposure to media and education of women had also played significant role in raising knowledge. Multivariate analysis suggested that the duration of credit program participation and exposure to media were significantly more likely to raise the health knowledge among women when the jilfluence of demographic and socio-economic factors were controlled. The paper concludes that micro-credit program can be an effective tool in promoting health among the poor women in Bangladesh.